An analytical study of the structure of Iraqi sport clubs and its relationship with the administrative creativity from the point of view of administrative association members - METEAB MUNAF, SUHAIR (International Journal of Psychosocial Rehabilitation, 2020)
Laying out the structural map for sports institutions, identifying all obstacles and problems, training workers on organization and development, and using advanced means and tools to strengthen communication networks, as well as the organizational structure and strategies used to develop administrative work and human resources, and investing the resources, stadiums and infrastructure owned by these clubs, which need to be organized and prioritized And the creativity of administrative sports an important role in facilitating things sports and filling all sports requirements required and giving administrators a yield of the level of achievement of the results of these clubs because they are responsible for the implementation of the club's policy And translating it into a practical reality while overcoming all difficulties and obstacles and facilitating work ,so the researcher found that it is better to delve into two important factors that may be related to important achievements at the administrative level, so the importance of research is evident by studying the requirements for structuring sports clubs and administrative performance from the point of view of members of the administrative body.